English as a foreign language teaching approaches in Saudi K–12 education: teacher-centered or student-centered - Alqahtani, Razan Mohammed; Alhamami, Munassir (Intelektual Pustaka Media Utama, 2024)
This study explores the educational methodologies employed by Saudi English as a foreign language (EFL) teacher, with a specific emphasis on contrasting teacher-centered approachand student-centered approach. Additionally, the research examines the teachers' personal beliefs regarding the most effective approach for implementation in EFL classrooms. To gather data, an online questionnaire was administered to 42 EFL teachers across Saudi K–12 schools in the Southern part of Saudi Arabia. The questionnaire comprised two sections: a demographic information segment and an inquiry into teachers' perspectives and practices. The results of the study showed a dichotomy. While a majority of participants professed that both teacher-centered and student-centered methodologies carry equal importance, a more nuanced picture emerged when examining their claimed practices versus actual classroom behavior. The majority of EFL K–12 instructors in Saudi classrooms leaned towards adopting teacher-centered approaches. These findings hold significant implications for EFL teacher training and professional development courses. This may be due to teachers' lack of confidence in implementing student-centered approaches, the traditional educational culture in Saudi Arabia, or pressure to prepare students for high-stakes exams. The study suggests that teacher education programs should focus on developing teachers' understanding and confidence in using student-centered approaches, and that the Ministry of Education should create a more supportive environment for student-centered teaching approaches.